2005
DOI: 10.1021/jp044847j
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Aggregates of the Carotenoid Zeaxanthin:  Time-Resolved Study of Excited States

Abstract: In this study, we present a way of controlling the formation of the two types of zeaxanthin aggregates in hydrated ethanol: J-zeaxanthin (head-to-tail aggregate, characteristic absorption band at 530 nm) and H-zeaxanthin (card-pack aggregate, characteristic absorption band at 400 nm). To control whether J- or H- zeaxanthin is formed, three parameters are important: (1) pH, that is, the ability to form a hydrogen bond; (2) the initial concentration of zeaxanthin, that is, the distance between zeaxanthin molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
94
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 43 publications
20
94
2
Order By: Relevance
“…To produce such large red shifts, a dramatic change in xanthophyll environment would be required, such as the appearance of a static dipole or point charge near the pigment responsible (41,42). An alternative explanation for a large red shift would be an excitonic splitting of the S 2 excited state of the xanthophyll (46). This so-called Davydov splitting is a result of strong Coulombic coupling between the excited states of closely associated molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To produce such large red shifts, a dramatic change in xanthophyll environment would be required, such as the appearance of a static dipole or point charge near the pigment responsible (41,42). An alternative explanation for a large red shift would be an excitonic splitting of the S 2 excited state of the xanthophyll (46). This so-called Davydov splitting is a result of strong Coulombic coupling between the excited states of closely associated molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Because zeaxanthin occupies a relatively peripheral position within the LHCII trimer (44), aggregation could result in close associations between xanthophylls belonging to neighboring trimers. Indeed, it has been shown that the formation of excitonically coupled J-aggregates of zeaxanthin (co-linear or "top-to-tail" chains of molecules) in water-ethanol mixtures gives rise to a red shift in the 0-0 transition to 535 nm (34,45,46), whereas lutein, antheraxanthin, and violaxanthin J-type aggregates possess red-shifted bands between 500 and 530 nm (45). In the following study, we specifically address the origin of ⌬A 525 .…”
mentioning
confidence: 99%
“…The absorption spectrum taken before precipitation shows a significant blue shift (compared to that of β-carotene in THF) that is reminiscent of formation of H-aggregates [51]. In contrast, β-carotene incorporated into aggregates From experiments with BChl c aggregates with quinones [31] we know that the changes in the Soret band upon aggregation are less pronounced than those in the Q y band.…”
Section: Our Results Show That β-Carotene Interacts With Bchl C Indumentioning
confidence: 98%
“…Effect of environment can hardly be responsible for such a change, because the S 1 lifetime of β-carotene is essentially insensitive to solvent properties [54]. It is known that aggregation of carotenoids induces changes in the S 1 lifetime and the decay becomes non-exponential due to annihilation [51]. Although the 6 ps lifetime observed here is comparable with the 5 ps component detected in J-aggregates of zeaxanthin [51], a carotenoid with spectroscopic properties nearly identical to those of β-carotene, the absence of annihilation in the intensity-dependent kinetics shown in Figure 5 makes aggregation of β-carotene as the reason for the S 1 lifetime shortening very unlikely.…”
Section: Our Results Show That β-Carotene Interacts With Bchl C Indumentioning
confidence: 99%
See 1 more Smart Citation